Sleep, quality of life and mood of nursing professionals of pediatric intensive care units - Priscilla Caetano Guerra; Nilton Ferraro Oliveira; Maria Teresa de Sande e Lemos Ramos Ascensão Terreri; Claudio Arnaldo Len (SciELO, 2016)
Abstract OBJECTIVE To assess sleep, quality of life and mood of nursing professionals of pediatric intensive care units. METHOD Quantitative, cross-sectional and descriptive study. Professionals grouped by morning, afternoon and evening shifts were assessed by means of the instruments: Morningness-Eveningness Questionnaire; Pittsburgh Sleep Quality Index; Epworth Sleepiness Scale; Generic questionnaire for the assessment of quality of life (SF-36); Beck Depression Inventory; Beck Anxiety Inventory; State-Trait Anxiety Inventory. RESULTS Sample consisted of 168 professionals, with prevalence of neutral typology (57.49%). There was no statistical significance regarding sleep, despite scores showing a poor quality of sleep and excessive daytime sleepiness for the three shifts. Quality of life did not reveal any statistical significance, but in the field "social role functioning" of the evening shift, a lower score was observed (p<0.007). There was no statistical significance regarding levels of anxiety and depression. CONCLUSION The results suggest that these professionals may present sleeping problems, but they do not have lower scores of quality of life or mood disorders. Likely explanations for these findings may include an adaptation to their work type over time and the fact that working with children is rewarding.